The Influence of the Read Answer Discuss Explain Create (RADEC) Learning Model on Elementary School Students' Numeracy Skills - Salshabylla, Dewi Mayang; Riyadi, Arie Rakhmat; Putri, Yasmin Gehan; Ulfiyani, Ulfiyani; Mardiah, Dede (International Conference on Elementary Education, 2025)
Based on the current international and national data, Indonesia has a low numeracy proficiency. This study aims to identify the potential of the (RADEC) Learning Model in efforts to enhance elementary school students' numeracy skills. Utilizing a pre-experimental approach, this research focuses on the implementation of RADEC within the context of Non-Standard Unit materials. The chosen methodology is the One-Group Pretest-Posttest design, applied to a sample of 18 elementary school students. Data analysis was conducted using inferential statistical methods, with the t-test as the primary tool to measure the increase in numeracy skills following the RADEC implementation. The results show a significant improvement, indicated by a t-value of 4.099, which is less than the t-table value of 2.110 at a 0.05 significance level. This conclusion leads to the rejection of H0 and acceptance of H1, significantly indicating that RADEC has a positive impact on improving students' numeracy skills.